Genome-Wide Investigation of the Cysteine Synthase Gene Family Shows That Overexpression of CSase Confers Alkali Tolerance to Alfalfa (Medicago sativa L.) - Yuan, Yuying; Song, Tingting; Yu, Jinqiu; Zhang, Wenkai; Hou, Xiangyin; Kong Ling, Zelai; Cui, Guowen (Frontiers in Plant Science, 2022)
Alfalfa is widely grown worldwide as a perennial high-quality legume forage and as a good ecological landcover. The cysteine synthase (CSase) gene family is actively involved in plant growth and development and abiotic stress resistance but has not been systematically investigated in alfalfa. We identified 39 MsCSase genes on 4 chromosomes of the alfalfa genome. Phylogenetic analysis demonstrated that these genes clustered into 6 subfamilies, and members of the same subfamily had similar physicochemical properties and sequence structures. Overexpression of the CSase gene in alfalfa increased alkali tolerance. Compared with control plants, the overexpression lines presented higher proline, soluble sugars, and cysteine and reduced glutathione contents and superoxide dismutase and peroxidase activities as well as lower hydrogen peroxide and superoxide anion contents after alkali stress. The relative expression γ-glutamyl cysteine synthetase genes (a downstream gene of CSase) in the overexpression lines was much higher than that in the control line. The CSase gene enhanced alkalinity tolerance by regulating osmoregulatory substances and improving antioxidant capacity. These results provide a reference for studying the CSase gene family in alfalfa and expanding the alkali tolerance gene resources of forage plants.